Financial Revolution: From Traditional Finance to Behavioral and Neuro-finance - Rashid, Mohammed; Ahmad, Rais; Tariq, Shazeb (South Asian Journal of Social Sciences and Humanities, 2022)
The paper aims to study the growth and evolution of finance, as well as how the evolution of finance theories aids investors in decision-making. The traditional finance model’s perfect mobility and rationality fail to predict the economic events, dot-com bubble, and the European debt crisis. These economic disasters provide the foundation for the development of behavioral finance. Psychology and finance are merged into behavioral finance. It defies the traditional financial premise. The field provides unique insights into financial and investment decision making models. Behavioral finance also serves as a bridge for developing novel financial solutions known as Neurofinance. Neurofinance employs neurotechnology to explain participants’ behaviour and predict their future behaviour based on observing their brains and hormonal activity.